Addressing the Missing Part of Evidence-based Practice: The Importance of Respecting Clinical Judgment in the Process of Adopting a New Screening Tool for Postpartum Depression. (2nd December 2017) - Ben-David, Vered; Jonson-Reid, Melissa; Tompkins, Ron
ABSTRACT: The aim of the present study was to examine the role of nurse's clinical judgment in the uptake of an evidence-based tool assessing postpartum depression, the Edinburgh Postpartum Depression Scale. Nurses in a home visitation program were being asked to regularly screen for postpartum depression. The screener was introduced as a new standard of practice for nurses. A qualitative investigation of the nurses' reactions in addition to an evidence-based screener was conducted. Prior to and during the implementation, several meetings were held with the nurses and the research team to discuss the nurses' experience with the tool. Nurses participated in semi-structured interviews and notes were reviewed to identify themes that may be useful in further understanding evidence-based practice in nurses' home visitation. It was found that the process of uptake included three phases: dissatisfaction with the utility of the tool; problem solving and integration of clinical judgment into a complementary instrument, and eventual reliance on the standardized tool. Respecting the nurses' field experience and clinical judgment was the key to the process of adoption of an evidence-based tool. The process uncovered here requires a larger scale study to see if this can be used across various settings and with differing screening mechanisms to increase comfort with the use of recommended non-health screening tools.